Evaluation of water ingress in cement treated material for durability assessments - Yeo, Y.; Nikraz, Hamid (2012)
Main Roads Western Australia currently prohibits the strength gained from cement modified materials to reduce pavement thickness due to the lack of durability of the cement treatment. It has been found both in Western Australia and internationally that the cement treatment of basecourse " disappears" due to a chemical retardation process known as carbonation. Carbonation occurs at the interface between cement matrices and pores with the presence of carbon dioxide in pore water. This paper therefore investigates the relationship between moisture ingress and cement content. The tube suction test and the unconfined compressive strength test are applied. The tube suction test measures the dielectric value, a measurement of electromagnetic wave reflection as an index of the performance of cemented basecourse. Subsequently, the sorptivity parameter is assessed which shows a correlation between the rate of water ingress and the square root of time. The results show that an increase in cement content proves to be beneficial in managing water ingress. © 2012 Institution of Engineers Australia.